(untitled) (Indonesian Art and Justice Review, 2024)
The relationship between art and the state in Indonesia has been fraught with political tension, especially in periods of authoritarian rule. This paper investigates how government intervention has shaped artistic expression and the boundaries of artistic freedom in Indonesia. Through an analysis of historical and contemporary examples, the paper explores how the Indonesian government has used censorship, regulation, and state-sponsored art to control and influence artistic production. It also looks at the role of resistance art in challenging state control and advocating for greater freedom of expression. The paper critically examines how art continues to be a site of struggle for autonomy and the preservation of creative freedom in an increasingly regulated cultural environment.